A concelebração eucarística como sinal privilegiado da unidade da Igreja: uma reflexão no horizonte da metafísica Zubiriana - Aguiar, Gilmar Antônio (2024)
It can be said that ecclesiastical unity is the founding reality of the Church, beauty and truth present in the Trinity. The Eucharist is the experience of thanksgiving where the one and same sacrifice unite everyone: the Paschal Mystery of Christ. The Eucharist is the gift of unity that brings together the people of God, celebrating the joy of encounter and new life in Christ. This celebration is enriched and enhances the unity of the Church when it is a concelebrated Mass, especially on the major feasts of the liturgical calendar. This wanted to resume and value the reform brought by the Second Vatican Council, especially with regard to the reformulation of the concelebrative act. Starting from the thoughts of Xavier Zubiri (1898-1983), this work aims to highlight the meaning and relevance of the Eucharistic Concelebration as a privileged sign of the unity of the Church, which is not just a note, even if essential, but an inherent condition of the essence of the Church, that is, unity as a transcendental reality that identifies, builds and manifests the Church in the world as a means of Redemption. In addition to the pastoral challenges and inherent demands, Eucharistic Concelebration remains a continuous line that leads us to value unity, communion and mission, as everyone is brothers and sisters and the Liturgy is the fundamental means to effect the participation of the people and rediscover the meaning and value of Christian spirituality.